Testing Women, Testing the Fetus : the Social Impact of Amniocentesis in America. - Rapp, Rayna (Taylor & Francis, 2000)
Rich with the voices and stories of participants, these touching firsthand accounts examine how women of diverse racial, ethnic, class and religious backgrounds perceive prenatal testing.